Family Experience Tracers: Patient Family Advisor led interviews generating detailed qualitative feedback to influence performance improvement - Kathryn Taff; Sheryl Chadwick; DeeJo Miller (The Beryl Institute, 2018)
Patient Family Advisors (PFAs) are integral partners in quality improvement processes at Children's Mercy Kansas City. Mimicking Joint Commission patient tracers, the Family Experience Tracer program was created to gather perspectives from end users of care and provide valuable insights regarding the patient experience. The Patient and Family Engagement team collaborates with departmental and organizational leadership to define the scope of the tracer project and determine meaningful topics to elicit feedback from patients and families. Tracers are conducted across the continuum of care and are led by a Patient Family Advisor to establish an immediate peer relationship. Patients and families provide detailed information in Family Experience Tracers, and CM acknowledges the importance of combining this information with other feedback sources to strengthen patient- and family-centered improvements.